Preliminary Environmental Assessment of Carbonated Slags as a Carbon Capture, Utilization, and Storage Materials (CCUS) - Ponnapat Watjanatepin; Laura Steinwidder; Anthony de Schutter; Giuseppe Granata; Sara Vicca; Tom Van Gerven; Karel Van Acker (Materials Proceedings)
The steel manufacturing industry is one of the most concentrated anthropogenic carbon-emitting point sources that is still expected to increase further each year. Moreover, steel slags are also generated at a rate of 10–20% of the total crude steel production. The possibility to valorize both the flue gases and steel slags through mineral carbonation has garnered the spotlight in recent research on waste valorization and sustainable steel production practices. Mineral carbonation of steel slags leads to the stable adsorption of carbon dioxide onto the surface of the steel slags. Nonetheless, it is essential to assess whether the environmental benefits resulting from the mineral carbonation process would outweigh the environmental burdens associated with the transformation and carbonation processes. To this end, this study aims to illustrate the potential environmentally friendly industrial waste valorization pathway by performing life cycle assessment (LCA) to obtain the environmental impacts of carbonated steel slags. The environmental impacts are calculated by the ReCiPe 2016 midpoint methodology. Furthermore, contribution analysis for the carbonated slag production is provided. This study also illustrates a comparison of steel slag carbonation with pure carbon and flue gases by means of scenario analysis. The results of this study should provide insights into the possibility of employing mineral carbonation on industrial wastes in the metallurgical sector as well as highlight the possible areas of improvement for prospective scale-ups. To this end, the results of this study could contribute to the improvement of the environmental sustainability of the steel manufacturing sector.